PEMANFAATAN LIMBAH CAIR TAHU SEBAGAI PEMACU PERTUMBUHAN BIBIT GERONGGANG (Cratoxylon arborescens) - Fiki Rangga Abdi; M. Mardhiansyah; Yossi Oktorini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Cratoxylon arborescens is a local tree of peat swamp forest that has the potential to be a candidate for planting in the initial phase of peat restoration. Quality seeds will be produced from well-managed nurseries. One aspect of nursery management is the provision of appropriate fertilizers and the right dosage. Giving this fertilizer can be done using tofu liquid waste. The purpose of this study was to determine the effect of tofu liquid waste on the growth of Cratoxylon arborescens seedlings and determine the best composition of tofu liquid waste to spur the growth of Cratoxylon arborescens seedlings. This research was conducted with a completely randomized design method (CRD), which consisted of 5 (five) treatments. Each treatment was repeated three times, so that 15 unit experiments could be obtained. Each experimental unit consists of five plants so that the total plant is 75 units. Concentration of tofu liquid waste for Cratoxylon arborescens seedlings is without giving (control), 20%, 40%, 60%, and 80%. The results showed that the application of tofu liquid waste affected the growth of Cratoxylon arborescens seedlings. The best composition of giving tofu liquid waste is giving tofu liquid waste as much as 20% (Treatment P1) with a yield of 100% life, height growth of 16.84 cm, seed diameter of 3.60 mm, plant dry weight of 4.18 gr and the top-root ratio of 2.72.Keywords : Cratoxylon arborescens, tofu liquid waste, Growth